Occurrence of Aflatoxin M1 in Raw and Processed Milk: A Contribution to Human Exposure Assessment After 12 Years of Investigation - Simona Summa; Sonia Lo Magro; Valeria Vita; Cinzia Franchino; Valentina Scopece; Pasqualino D’Antini; Marco Iammarino; Rita De Pace; Marilena Muscarella (Applied Sciences)
The aim of this study was to estimate the aflatoxin M1 (AFM1) contamination in raw milk and processed milk (pasteurized or UHT) collected from two regions in Italy (Puglia and Basilicata) during a 12-year period: 2012–2023. A total of 1017 milk samples were analyzed first proceeding with screening analysis by enzyme-linked immunosorbent assay (ELISA), and suspected non-compliant samples (AFM1 concentration higher than 0.042 µg/kg) were then analyzed by high performance liquid chromatographic with fluorimetric detection (HPLC/FLD) confirmation method. AFM1 concentration ≥ 0.005 µg/kg (ELISA limit of quantitation) was detected in 553 of the 1017 milk samples (54.4%). AFM1 levels exceeding the European Union maximum limit (ML) of 0.050 µg/kg were detected in 70 samples, 49 of which were determined as non-compliant samples (4.8%). Particularly high concentrations of AFM1, exceeding 200 µg/kg, were found in four samples, three raw milk and one pasteurized. Regarding this risk exposure study, only the MOE values obtained under “high exposure scenario” were lower than 10,000, while those calculated from the overall mean values resulted as not of concern.